2007
DOI: 10.1021/es0713936
|View full text |Cite
|
Sign up to set email alerts
|

A New Role for Sulfur in Arsenic Cycling

Abstract: Sulfur and arsenic often coexist in the environment and share similar microbial redox transformations. We examined the effects of sulfide on aerobic arsenite oxidation in alkaline lake water samples and in laboratory enrichment cultures. Significant arsenite oxidation occurred only in treatments with bacteria present, and production of arsenate was greatly enhanced by the addition of sulfide or thiosulfate. IC-ICP-MS analysis of samples showed that mono- and dithioarsenate formed in arsenite + sulfide amended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 28 publications
4
59
0
1
Order By: Relevance
“…Are these compounds true enzymatic inhibitors? A concentration of 60 M sulfide has been observed to completely stop As III oxidation in whole cells of Hydrogenobaculum at low pH (48), whereas sulfide has been reported to strongly enhance the As III oxidation in Mono Lake samples at high pH (58). However, did sulfide act on the Aro directly in these cases?…”
Section: IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Are these compounds true enzymatic inhibitors? A concentration of 60 M sulfide has been observed to completely stop As III oxidation in whole cells of Hydrogenobaculum at low pH (48), whereas sulfide has been reported to strongly enhance the As III oxidation in Mono Lake samples at high pH (58). However, did sulfide act on the Aro directly in these cases?…”
Section: IIImentioning
confidence: 99%
“…However, did sulfide act on the Aro directly in these cases? Sulfide has been shown to react with As III , forming orpiment at low pH (59) and thioarsenic species at high pH (58,60). In these three cited works, sulfide was added in equal if not higher quantities compared with As III , allowing the product of the reaction between As III and sulfide to significantly modify the As III quantity available for Aro-mediated oxidation.…”
Section: IIImentioning
confidence: 99%
“…It is likely that As shares similar microbial redox transformations with sulfur (S) (Fisher et al 2008). The reduction of arsenate (As(V)) to As(III) and reductive dissolution of iron oxyhydroxides facilitate As release from soil iron oxyhydroxides to the soil solution (Poulton et al 2004;Hoeft et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial SO 4 2− reduction to sulfide (S 2− ) can immobilize As by facilitating the precipitation of As sulfide and Fe sulfide minerals. The reported iron and arsenic sulfide secondary minerals included mackinawite, siderite, orpiment, and thioarsenites (Kirk et al 2004;Fisher et al 2008;Burton et al 2013Burton et al , 2014. It is reported that microbial SO 4 2− reduction leads to lower concentrations of porewater Fe(II) and As in a flooded soil, as a result of mackinawite formation and As co-precipitation (Burton et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3c, 19 The changes in As(III) and As(V) concentrations indicate the cycling of the As species and the formation and degradation of As-S products as time passes. The eluent pH was maintained at 10 as this has been reported to maintain thioarsenic species and this could have brought about further changes to the speciation on the column.…”
Section: B3cmentioning
confidence: 99%